Effect of seasonality and Cr(VI) on starch-sucrose partitioning and related enzymes in floating leaves of Salvinia minima - Rosa, Mariana (2017)
Effects of seasonality and increasing Cr(VI) concentrations on leaf starch-sucrose partitioning, sucrose- and starch-related enzyme activities, and carbon allocation toward leaf development were analyzed in fronds (floating leaves) of the floating fern Salvinia minima. Carbohydrates and enzyme activities of Cr-exposed fronds showed different patterns in winter and summer. Total soluble sugars, starch, glucose and fructose increased in winter fronds, while sucrose was higher in summer ones. Starch and soluble carbohydrates, except glucose, increased under increasing Cr(VI) concentrations in winter fronds, while in summer ones only sucrose increased under Cr(VI) treatment. In summer fronds starch, total soluble sugars, fructose and glucose practically stayed without changes in all assayed Cr(VI) concentrations. Enzyme activities related to starch and sucrose metabolisms (e.g. ADPGase, SPS, SS and AI) were higher in winter fronds than in summer ones. Total amylase and cFBPase activities were higher in summer fronds. Cr(VI) treatment increased enzyme activities, except ADPGase, in both winter and summer fronds but no clear pattern changes were observed. Data of this study show clearly that carbohydrate metabolism is differently perturbed by both seasonality and Cr(VI) treatment in summer and winter fronds, which affects leaf starch-sucrose partitioning and specific leaf area (SLA) in terms of carbon investment.